Measures of the Determinants of Demand for Personal Healthcare Services Delivery in Nigeria - Dr Umanhonlen Felix Ogbeiyulu (Publication of the European Centre for Research Training and Development -UK. International Journal of Health and Psychology Research, 13(1), 106-157, 2025, 2025)
This study sought to assess the relationship between the determinants of demand for personal healthcare services delivery in Nigeria. The main objective of the study was to assess the determinants of demand for personal healthcare services delivery in Nigeria. The specific objectives were to examine the relationship between literacy; income; environmental factors, government and private expenditures on health in Nigeria. Specifically, the study is a descriptive statistics research with the use of secondary sources of data from the World Health Development Indicators (WDI) and Central Bank of Nigeria (CBN) bullettins. The study adopted Pooled Ordinary Least Square (OLS) regression model and Autoregressive Distributed Lag Model (ARDL). The analysis was based on annual time series data for the period of 1990 to 2023. The result revealed that literacy rate has a significant negative relationship with demand for personal healthcare services in Nigeria, which implies that literacy rate in Nigeria directly contributed to the decline of private demand for personal healthcare services over time. The study also observed that per capita income has a significant positive relationship with demand for personal healthcare services, which means that a rise in income levels increases demand for private health expenditure in Nigeria. Moreso, the study found that there is actually no significant relationship between environmental factor and demand for personal healthcare services in Nigeria. Finally, the study shows that government expenditure on health significantly reduces demand for personal healthcare services in Nigeria. Therefore, government health expenditure is a substitution for private health expenditure in Nigeria over time. It concludes that demand for personal healthcare services requires a deep evaluation of public health investments, economic growth policies and educational reforms. It suggested that there is the need to focus on health promotion campaigns at all levels of governance in Nigeria, and however, policies that combine literacy initiatives with health promotion campaigns can both improve demand for quality healthcare services at the private level and also ensure healthier lifestyles and preventive care.
Health Economics and Psychology Research,
Keywords: private expenditure; healthcare; delivery; literacy; demand; income; healthcare services; personal services; inflation; environmental factors; government expenditures